2011
DOI: 10.1086/660098
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Wide Reduction in Central Line–Associated Bloodstream Infections: A Tale of Two Small Community Hospitals

Abstract: Despite increasing awareness of central line-associated bloodstream infections (CLABSIs) in general wards, published strategies come from intensive care units (ICUs) of large tertiary care centers. After implementing a central line insertion checklist, two community hospitals experienced an 86% reduction in CLABSI rates in ICUs and a 57% reduction in non-ICU settings over 36 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The prevention and control of CVC-ABSIs has rarely been investigated outside the ICU setting, and to our knowledge, there is only one study conducted at two small community hospitals demonstrating 57% CVC infection rate reduction in non-ICU CVC-ABSIs, with the use of antibiotic impregnated catheters for some patients [12]. In this series the use of CVC, as we also reported, was higher in non-ICU setting, and considering that the vast majority of all hospitals are community hospitals with fewer than 200 beds, these results reinforce the necessity and importance of restoring measures of prevention and control in non-ICU inpatient [6,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention and control of CVC-ABSIs has rarely been investigated outside the ICU setting, and to our knowledge, there is only one study conducted at two small community hospitals demonstrating 57% CVC infection rate reduction in non-ICU CVC-ABSIs, with the use of antibiotic impregnated catheters for some patients [12]. In this series the use of CVC, as we also reported, was higher in non-ICU setting, and considering that the vast majority of all hospitals are community hospitals with fewer than 200 beds, these results reinforce the necessity and importance of restoring measures of prevention and control in non-ICU inpatient [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Although a standard control group for comparison purposes was not feasible, the fact that a progressive and largely consistent increase in CVC-ABSIs rates from 1991 to 2008 and a decrease in CVC-ABSIs rates was observed for three years after starting the intervention programme, could support a cause and effect relationship between the beginning of a programme called “bacteremia zero” and a decrease in outside ICU CVC-ABSIs rates in Internal Medicine wards. The effects of this intervention and the increase in CVC-ABSIs rates during summertime reinforce the importance of allocating only trained and competent personnel for insertion and maintenance of central intravascular catheters, and ensuring appropriate nursing staff levels in non-ICU settings [2,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Multifaceted infection prevention programs integrating target DA-HAI surveillance methods were proved effective in several United States studies, which showed the occurrence of DA-HAI could be reduced by more than 30%, along with an analogous reduction in DA-HAI-related hospital costs[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the US studies of 5 units demonstrating the greatest success in preventing CLABSI 56,62,65,78,83 and CAUTI, 28,34,66,134 several shared features emerged. Interventions that addressed multiple steps within the life cycle of a catheter (avoidance, insertion, maintenance, and removal) were common.…”
Section: Discussionmentioning
confidence: 99%
“…Study designs included 14 randomized controlled trials (RCTs) 48,64,68,74,79,[90][91][92][93][94][95][96][97][98] and 88 before-after studies (Appendix Table 1). 10,14,16,[24][25][26][27]33,[38][39][40][41][42][43][44][45][46][47][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][69][70][71][72]…”
Section: Characteristics Of Included Central Vascular Catheter Infectmentioning
confidence: 99%